Burnout and work-life balance among physicians: the role of migration background - Hussenoeder, Felix S. (J Occup Med Toxicol, 2021)
BACKGROUND: We want to analyze the effect of migration background (MB) on physician burnout and work-life balance. METHODS: In September 2019, physicians from various specialties answered a questionnaire on work and health. We analyzed a subsample of 526 physicians that were working full time in a hospital, 14% with an MB and 47.9% were female. RESULTS: Multivariate analysis showed that physicians with an MB exhibit significantly less favorable scores on all three burnout dimensions, and this effect persisted in the regression analysis after adding age, gender, and marital status as control variables. There were no differences with regard to work-life balance. CONCLUSIONS: To our knowledge, our study is the first one to suggest that MB plays a significant role in physician mental health. Future research will benefit from identifying the factors behind that connection, e.g., problems related to acculturation, communication and social integration, which can then be addressed by policymakers in order to maintain and improve the medical infrastructure.